2021
DOI: 10.12717/dr.2021.25.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Formyl Peptide Receptor 2 Retards Hair Regeneration by Modulating the Activation of Hair Follicle Stem Cells and Dermal Papilla Cells in Mice

Abstract: Hair loss is one of the most common chronic diseases, with a detrimental effect on a patient's psychosocial life. Hair loss results from damage to the hair follicle (HF) and/or hair regeneration cycle. Various damaging factors, such as hereditary, inflammation, and aging, impair hair regeneration by inhibiting the activation of hair follicle stem cells (HFSCs) and dermal papilla cells (DPCs). Formyl peptide receptor 2 (FPR2) regulates the inflammatory response and the activity of various types of stem cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Recently, it has also been reported that FPR2 is involved in regulating the migration and proliferation of many types of stem cells. Han et al [ 14 ] found that the proliferation of hair follicle stem cells and dermal papilla cells in Fpr2 -/- mice was significantly reduced, which induced hair loss. Chen et al [ 15 ] found that Fpr2 -/- mice displayed shortened colonic crypts and reduced acute inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has also been reported that FPR2 is involved in regulating the migration and proliferation of many types of stem cells. Han et al [ 14 ] found that the proliferation of hair follicle stem cells and dermal papilla cells in Fpr2 -/- mice was significantly reduced, which induced hair loss. Chen et al [ 15 ] found that Fpr2 -/- mice displayed shortened colonic crypts and reduced acute inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%